Cuadro signos - Paz, Milo.; Ilagan, Bonifacio P.; Magtoto, Bing.; Center for Environmental Concerns (Manila CEC and AsiaVisions Media Foundation, 1995)
A documentary showing the ravages wrought on four Philippine ecosystems by industrialization. The featured ecosystems are the fishing villages of Naujan in Oriental Mindoro and Cordova in Mactan, Cebu, and the farming communities of Pardo in Cebu and Polomolok in South Cotabato.
Sangkahig, santuka (10 mins.) -- Buhay at kamatayan ang puhunan (12 mins.) -- Wala nang bundok, wala nang dagat (11 mins.) -- Hindi na magtatagal (15 mins.)
VHS.
Filipino subtitles.
Keywords: Environmental degradation -- Philippines; Sustainable development -- Philippines; Environmental sciences